Method of successive approximations for abstract volterra equations in a banach space - Mishura, Yu. S.; Tomilov, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We apply the method of successive approximations to abstract Volterra equations of the formx=f+a*Ax, whereA is a closed linear operator. The assumption is made that a kernela is continuous but is not necessarily of bounded variation.